Legal Protection for Notaries in Making Authentic Deeds in Indonesia - Arief Budiono; Dito Pratama Adi Sugiarto; Syaifuddin Zuhdi (Universitas Internasional Batam, 2023)
A notary is a public official who has the authority to create an authentic deed and has other authority. This statement is stated in Article 1 of Law No. 2 of 2014 concerning Amendment to Law No. 30 of 2004 concerning Notary positions (hereinafter referred to as Law No. 2 of 2014). But there many cases about notary create authentic deed without any regards to ethics and fact. This problem actually a gap from this research. Gap from Law in the book and law in the practices. This type of study uses normative legal research. This study used two approaches, namely Conceptual Approach and Statute Approach. The specifications of this study are descriptive of analysis and qualitatively analyzed methods. Notary is required to be responsible for the deed she made, Notary runs her profession often subject to articles 263, 264, and 266 Jo Article 55 of the Criminal Code. The Notary Office Act does not specifically regulate the protection of the notary's law in the process of examining false information. The process of examining the Honorary Assembly does not provide legal protection, because the Law does not clearly regulate the protection law for Notary in criminal cases.